Legal Protection of Illegal Migrant Workers in Nunukan District - Yahya Ahmad Zein; Putra Kurnia, Mahendra; Heni Sutra (Faculty of Law, Mulawarman University, 2021)
Nunukan Regency, which borders Sabah and Sarawak, Malaysia has problems regarding the repatriation of Indonesian Citizens in the capacity as Indonesian Migrant Workers who working in Malaysia. The repatriation is related to immigration violations such as not having complete documents to enter Malaysian territory as a worker, so it can be categorized as illegal Indonesian Migrant Workers. This research uses a doctrinal approach by reviewing the regulations related to migrant workers plus analysis of documents and data obtained from in-depth interviews with the Placement and Protection of Indonesian Migrant Workers Agency in Nunukan and Immigration in Nunukan. Legal protection for illegal Indonesian Migrant Workers through the Placement and Protection of Indonesian Migrant Workers Agency and Immigration in Nunukan is taken in 3 (three) ways, (1) prevention of non-procedural illegal Indonesian Migrant Workers; (2) deportation; and (3) the return of illegal Indonesian citizens/Indonesian Migrant Workers to their hometown. The efforts to protect the law are coupled with the closure of illegal cross-border routes between Indonesia and Malaysia in the Nunukan Regency area. It is hoped that all legal protection efforts will minimize the presence of illegal Indonesian Migrant Workers.